2006
DOI: 10.1111/j.1469-7580.2006.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Keystones in lymph node development

Abstract: New molecular markers are constantly increasing our knowledge of developmental processes. In this review article we have attempted to summarize the keystones of lymphoid tissue development in embryonic and pathological conditions. During embryonic lymph node development in the mouse, cells from the anterior cardinal vein start to bud and sprout, forming a lymph sac at defined sites. The protrusion of mesenchymal tissue into the lymph sacs forms the environment, where so-called 'lymphoid tissue inducer cells' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 88 publications
0
35
0
Order By: Relevance
“…Early LyveI ϩ lymph sac cells give rise to both mesenchymal organizer cells and LECs during later LN development. 35 The stromal cell progenitor fate-mapping analysis in embryonic and neonatal LNs, as revealed by the IL-7-Cre transgene, showed that IL-7 promoter activity was almost exclusively restricted to the LEC differentiation pathway. We therefore conclude that IL-7 expression in FRCs, as shown here (and by Link et al 20 ) appears to be a process that is restricted to later stages of LN development (ie, during colonization of LNs by lymphocytes and during adaptive remodeling processes).…”
Section: Discussionmentioning
confidence: 99%
“…Early LyveI ϩ lymph sac cells give rise to both mesenchymal organizer cells and LECs during later LN development. 35 The stromal cell progenitor fate-mapping analysis in embryonic and neonatal LNs, as revealed by the IL-7-Cre transgene, showed that IL-7 promoter activity was almost exclusively restricted to the LEC differentiation pathway. We therefore conclude that IL-7 expression in FRCs, as shown here (and by Link et al 20 ) appears to be a process that is restricted to later stages of LN development (ie, during colonization of LNs by lymphocytes and during adaptive remodeling processes).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the lymph node begins at around E10.5 by the budding and sprouting of the lymphendothelial precursor cells from arterial cardiac vein, which later differentiate into lymphatic and blood vascular endothelial cells. The hematopoietic progenitor lymphoid tissue inducer cells arrive at the developing lymph nodes at E12.5-E14.5 (Cupedo et al, 2004;Blum and Pabst, 2006;Drayton et al, 2006). Arf6 mRNA was weakly positive throughout the tissue at E15.5 (Fig.…”
Section: Expression In the Immune Systemsmentioning
confidence: 99%
“…I n t e s t i n a l l y m p h o i d a g g r e g a t e s ( i L A s ) c a n b e discriminated from PP, which comprises iLF and CP that are closely associated with the epithelial lining in the small and large intestine [30] . CP were defined as tiny aggregates of c-Kit + IL-7R + cells [31] , whereas iLFs are constituted by solitary B follicles that are localized in the anti-mesenteric regions of the intestinal wall, and contain small numbers of mature T lymphocytes, but also c-Kit + and IL-7R + cells [32][33][34] .…”
Section: Dcs In Intestinal Lymphoid Tissuesmentioning
confidence: 99%